Microfluidic Encapsulation of Single Cells by Alginate Microgels Using a Trigger-Gellified Strategy - Shao, Fei; Yu, Lei; Zhang, Yang; An, Chuanfeng; Zhang, Haoyue; Zhang, Yujie; Xiong, Yi; Wang, Huanan (Frontiers in Bioengineering and Biotechnology, 2020)
Microfluidics-based alginate microgels have shown great potential to encapsulate cells in a high-throughput and controllable manner. However, cell viability and biological functions are substantially compromised due to the harsh conditions for gelation, which remains a major challenge for cell encapsulation. Herein, we presented an efficient and biocompatible method by on-chip triggered gelation to generate microfluidic alginate microgels for single-cell encapsulation. Two calcium complexes of calcium–ethylenediaminetetraacetic acid (Ca-EDTA) and calcium–nitrilotriacetic (Ca-NTA) as crosslinkers for triggered gelation of alginate were compared and investigated for feasible application. By triggered release of Ca2+ ions from the calcium complex via adding acetic acid in the oil phase, the alginate precursor in the aqueous droplets can be crosslinked to form alginate microgels. Although using Ca-EDTA and Ca-NTA both achieved on-chip gelation, Ca-NTA led to significantly higher cell viability since the dissociation of Ca2+ ions from Ca-NTA can be obtained using less concentration of acid compared to Ca-EDTA. We further demonstrated the functionality of encapsulated mesenchymal stem cells (MSCs) in alginate microgels prepared using Ca-NTA, as evidenced by the osteogenesis of encapsulated MSCs upon inductive culture. In summary, our study provided a biocompatible strategy to prepare alginate microgels for single-cell encapsulation which can be further used for applications in tissue engineering and cell therapies.